Are digital natives overconfident in their privacy literacy? Discrepancy between self-assessed and actual privacy literacy, and their impacts on privacy protection behavior - Ma, Shuai; Chen, Chen (Frontiers in Psychology, 2023)
Privacy literacy is recognized as a crucial skill for safeguarding personal privacy online. However, self-assessed privacy literacy often diverges from actual literacy, revealing the presence of cognitive biases. The protection motivation theory (PMT) is widely used to explain privacy protection behavior, positing that whether individuals take defensive measures depends on their cognitive evaluation of threats and coping capabilities. However, the role of cognitive biases in this process has been understudied in previous research. This study focuses on Chinese digital natives and examines the differential impacts of subjective and objective privacy literacy on privacy protection behavior, as well as the role of cognitive biases in privacy decision-making. The results show that there is no significant correlation between subjective and objective privacy literacy, and a bias exists. When privacy concern is used as a mediating variable, there are significant differences in the paths through which subjective and objective privacy literacy influence privacy protection behavior. Furthermore, privacy literacy overconfidence moderates the relationship between privacy concern and privacy protection behavior. The findings confirm the influence of cognitive biases in privacy behavior decision-making and extend the PMT. This study also calls for the government to enhance privacy literacy training for digital natives to improve their privacy protection capabilities.